Estimation of end-of-life electric vehicle generation and analysis of the status and prospects of power battery recycling in China - Li, Yang (Waste management & research : the journal of the International Solid Wastes and Public Cleansing Association, ISWA, 2022)
With the development of the electric vehicle (EV), vehicle end-of-life (EOL) management has become a significant challenge. This study sets two EV sales scenarios (low and high), compares the impact of two battery replacement methods (buying a new vehicle or replacing the battery) on future EOL EV production, and predicts the difference in the amount of EOL EV battery production under two probability functions (normal and Weibull's distributions). The results show that when the EV power battery is retired and the vehicle owner chooses to buy a new vehicle, the predicted scrap quantity under low sales and high sales (HS) scenarios in 2030 is 4.3 and 5.3 million, respectively. Replacing the battery and continuing to use the vehicle will mean fewer EOL vehicles are generated. Considering the construction of an EOL EV battery recycling management system in China is still in the exploratory period, it is necessary to encourage vehicle owners to replace the battery and continue to use the vehicle. Under a HS scenario, the predicted number of EOL EV batteries in 2030 is 3.8-7.4 million. In the next 10 years, the issue of EV recycling should be raised to the same level as the issue of EV popularisation